Fibroblast and pre-osteoblast cell adhesive behavior on titanium alloy coated with diamond film - Silva,William de Melo (2017)
It is well known that titanium alloys have mechanical strengths comparable to steels, as well as high corrosion resistance. Also, they have the advantage of promoting osseointegration, when used in medical and dental implants. This work aims to describe the adhesion properties of fibroblast and osteoblast cells on the surface of titanium aluminum vanadium alloy (Ti6Al4V). Three different conditions of the surface were investigated: smooth, rough and covered with diamond film. Conventional material characterizations were performed to the film which consisted in: Morphological visualization by scanning electron microscopy, confocal profilometry, X-ray diffraction pattern, Raman backscattering spectroscopy and atomic force microscopy. Biocompatibility tests of Ti6Al4V were performed using primary human fibroblasts and mouse pre-osteoblasts cell line MC3T3-E1. Overall, diamond films deposited on Ti6Al4V showed interesting results of uniformity and protection against cracks on to the surface, reasonable biocompatibility features if compared to uncovered ones, indicating that this film is an alternative for using in health care applications.